Emergent normal-state Mottness in the infinite-layer NdNiO_{2} superconductor - L. Craco; A. S. de Arruda; S. Leoni (Physical Review Research, 2022)
We present a computational study based on density functional plus dynamical mean-field theory calculations for the normal-state electronic reconstruction of pure and hole-doped NdNiO_{2} superconductors. Our results capture the T dependence of the electrical resistivity, providing a many-particle interpretation of the emergence of pseudogaplike features at low energies as well as the weakly insulating regime seen in experiment. We show how Mottness manifests itself in the weak localization to bad-metallicity crossover due to strong correlation in the e_{g}-shell one-particle spectral functions and self-energies.